2018
DOI: 10.12740/pp/68611
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of the Montreal Cognitive Assessment 7.2 and the Mini-Mental State Examination in the detection of mild neurocognitive disorder in people over 60 years of age. Preliminary study.

Abstract: Cel pracyAnaliza wiarygodności polskiej wersji MoCA 7.2 vs. MMSE w wykrywaniu łagodnych NCD z uwzględnieniem czułości i swoistości według punktów odcięcia.MetodaBadanie przekrojowe przeprowadzono na Katedrze i Klinice Geriatrii Collegium Medicum w Bydgoszczy, Uniwersytety Mikołaja Kopernika. Czas trwania badania wrzesień 2014 – grudzień 2015. W badaniu wzięło udział 131 uczestników, w tym 54 osoby przydzielono do grupy bez NCD, zaś 77 do grupy z mild NCD. Rekrutacja do obu grup odbywała się w oparciu o szczeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Although the MMSE is the commonly used scale for evaluating cognitive function, it is claimed to be imprecise for detecting early and mild cognition impairment. 32 In conclusion, our long-term follow-up analysis of a single-center cohort of the MT103-104 phase 1 trial revealed that blinatumomab is a highly effective CD19-targeting bispecific antibody capable of inducing durable remissions in heavily pretreated patients with advanced-stage R/R B-NHL. This also applies to lymphoma regardless of tumor burden.…”
Section: Discussionmentioning
confidence: 74%
“…Although the MMSE is the commonly used scale for evaluating cognitive function, it is claimed to be imprecise for detecting early and mild cognition impairment. 32 In conclusion, our long-term follow-up analysis of a single-center cohort of the MT103-104 phase 1 trial revealed that blinatumomab is a highly effective CD19-targeting bispecific antibody capable of inducing durable remissions in heavily pretreated patients with advanced-stage R/R B-NHL. This also applies to lymphoma regardless of tumor burden.…”
Section: Discussionmentioning
confidence: 74%
“…Information of each study including the objective, clinical characteristics of the sample, main outcomes, and results is presented in Table 1. The Mini-Mental State Examination [49] was the most widely used tool to determine the severity of the NCDs with a wide range in the scores (10–30), followed by the Montreal Cognitive Assessment [50] with scores ranging from 18 to 30 points. Outcome measures include traditional neuropsychological tests (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of the Polish version of the MoCA 7.2 was analyzed by Sokolowska and colleagues, who demonstrated that the MoCA detects MCI with a sensitivity of 89.5% and a specificity of 74.1 at a cutoff point of 24 or below. In this study, the recommended cutoff point for the MoCA resulted in a sensitivity of 43.3% [ 43 ]. Identification of MCI was based on the DSM-5 criteria [ 73 ].…”
Section: Montreal Cognitive Assessment (Moca)mentioning
confidence: 99%